Facile synthesis of nanostructured WO3 thin films and their characterization for ethanol sensing. - Yaacob, Mohd. Hanif; Ahmad, Muhammad Zamharir; Sadek, Abu Z.; Jian, Z. Ou; Latham, Kay; Wlodarski, Wojtek (2013)
A simple technique to fabricate nanostructured WO3 thin films onto conductomeric transducers has been employed for ethanol sensing application. Initially, pure tungsten (W) thin films were deposited onto the substrate employing RF sputterer and followed by an etching process. Three types of etching agent were used: nitric (HNO3), sulphuric (H2SO4), and phosphoric (H3PO4) acid. It was found that the surface morphology and crystallinity of the WO3 films were heavily dependant to the etchants employed during the fabrication process. The developed sensors were tested towards ethanol vapor of different concentrations (10–200 ppm) at temperatures between room and 450 °C. The sensors showed stable and reproducible response at optimum operating temperatures. High sensor response towards vaporized ethanol as well as fast τres and τrec was observed during the “adsorption” and “desorption” interval. The recorded maximum response for these devices when exposed towards 100 ppm ethanol was measured to be 8 (Ro = 4.6 kΩ), 5.8 (Ro = 22.5 GΩ), and 5 (Ro = 0.29 MΩ) for HNO3, H3PO4, and H2SO4, respectively. The optimum operating temperatures were determined to be 400, 300–380, and 360 °C for the sensors developed using HNO3, H3PO4, and H2SO4, respectively.